Encapsulation of the Dinuclear Trithiolato‐Bridged Arene Ruthenium Complex Diruthenium‐1 in an Apoferritin Nanocage: Structure and Cytotoxicity. (11th February 2019) - Petruk, Ganna; Monti, Daria Maria; Ferraro, Giarita; Pica, Andrea; D'Elia, Luigi; Pane, Francesca; Amoresano, Angela; Furrer, Julien; Kowalski, Konrad; Merlino, Antonello
Abstract: The effects of encapsulating the cytotoxic dinuclear trithiolato‐bridged arene ruthenium complex [(η 6 ‐ p ‐MeC6 H4 i Pr)2 Ru2 (μ2 ‐S‐ p ‐C6 H4 t Bu)3 ]Cl (DiRu‐1) within the apoferritin (AFt) nanocage were investigated. The DiRu‐1‐AFt nanocarrier was characterized by UV/Vis spectroscopy, ICP‐MS, CD and X‐ray crystallography. In contrast to previously reported Au‐ and Pt‐based drug‐loaded AFt carriers, we found no evidence of direct interactions between DiRu‐1 and AFt. DiRu‐1‐AFt is cytotoxic toward immortalized murine BALB/c‐3T3 fibroblasts transformed with SV40 virus (SVT2) and human epidermoid carcinoma A431 malignant cells, and exhibits moderate selectivity for these cancer cells over normal BALB/c‐3T3 cells. DiRu‐1‐AFt triggers the production of reactive oxygen species, depolarization of mitochondrial membrane potential, and induces cell death via p53‐mediated apoptosis. Comparison between our data and previous results suggests that the presence of specific interactions between a metal‐based drug and AFt within the protein cage is not essential for drug encapsulation. Abstract : Caged, but uncoordinated : The effects of encapsulating the cytotoxic dinuclear trithiolato‐bridged arene ruthenium complex [(η 6 ‐ p ‐MeC6 H4 i Pr)2 Ru2 (μ2 ‐S‐ p ‐C6 H4 t Bu)3 ]Cl (DiRu‐1) within an apoferritin (AFt) nanocage were investigated. Comparison of our data with previous results suggests that the presence of specific interactions between a metal‐based drug and AFt within the protein cage is not essential for drug encapsulation.